Penanaman Nilai-Nilai Multikultural: Studi Kasus Pada Pesantren Nabil Husein Samarinda Kalimantan Timur - Khojir, Khojir (IAIN Samarinda, 2014)
Pesantren Nabil Husein is the biggest pesantren in Samarinda. It is not only because of the wide area of it, but it is also because of the total number of its students as well as its programs. Its students and teachers are from different places and educational background. This study tried to describe the media and the model in the teaching of multiculturisme values at Pesantren Nabil Husein Samarinda. This is a sociological and pehenomenological qualititave research. The data and data sources were from the ustadz, the headmasters, the owner, the managerial staffs, and the students. The data sampling technique used purposive sampling. The data collection used interview, observation, and documentation. The data validation used data triangulation. The data were analyzed by using three stages of data analysis, they are: data reduction, data display, and coclusion drawing. The result of the study shows that: 1) the media used to reinforce the multiculturisme values are the students’ orientation activity, dormitory, ta’lim al-Diniyah, art and culture performances, and halaqah; 2) the model used to reinforce the multiculturalisme values are the action-reflection and action model, ignasian and practice model, empirical model, and rasional model. Based on the findings, it is suggested the dormitory managerial staffs become more intensive in reinforcing the multiculturalisme values especiallyat al-Azhar room, all teachers and managerial staffs should have a same vision in reinforcing the multiculturalisme values, and the non-academical activities should be improved in reinforcing the multiculturalisme values.